Measurement of phase-energy electron distribution at the RF gun exit using alfa-magnet - Kushnir, V.A.; Mitrochenko, V.V. (Вопросы атомной науки и техники, 2004)
The paper presents the results of measuring the electron phase-energy distribution at the exit of the S-band
nanosecond photo RF gun. The RF gun is the electron source of the injector system of linac LU-60. The main
bunching and selection of longitudinal moments occur in the nonisochronal magnetic system named as α-magnet.
The method of measuring the phase-energy distribution is based on selection of properties of a bunching system. В роботі приведено результати вимірювання фазо-енергетичного расподілу електронів на виході
наносекундної ВЧ гармати десятисантиметрового диапазону. Метод вимірювання базується на селектуючих
властивостях неїзохронного магнітного группирователя – альфа-магніту. В работе приведены результаты измерения фазо-энергетического распределения электронов на выходе
наносекундной фотоэмиссионной ВЧ пушки десятисантиметрового диапазона. Предложенный метод измерения фазо-энергетического распределения базируется на селектирующих свойствах неизохронного магнитного группирователя – альфа-магнита.